Elastolytic activity is associated with inflammation in bladder cancer. (24th June 2021) - Gruba, Natalia; Stachurski, Lech; Lesner, Adam
Abstract: Cancer development and progression is often associated with inflammation. Late diagnosis of inflammation that directly leads to the development of neoplasm—cancer is associated with a reduction in the chance of successful treatment or is associated with therapeutic difficulties. A panel of chromogenic substrates was used for the qualitative determination of the specific activity of enzymes in urine of patients with confirmed inflammatory reaction and/or epithelial neoplasms in particular tumours at various stages of development. Urine of people with excluded inflammation was used as a control group. Proteolytic activity was determined in urine samples collected from patients with epithelial neoplasms and/or inflammation. What is more, we determine human neutrophil elastase activity-related inflammation based on the examination of urine samples. We suspect that the proteolytical activity of urine samples is due to neutrophil response to inflammation, which is directly related to cancer. This is the first study to determine elastolytic activity in bladder cancer urine samples. It supports wider use of urine for inflammation screening.